Economic and social development towards a sustainable direction in Van Lam Embroidery village (Ninh Hai, Hoa Lu, Ninh Binh) : Luận văn ThS. Khu vực học: 60 31 60 - Đo, Thi Hong Thu (Viện Việt Nam học và Khoa học Phát triển, 2017)
98 p. + CD-ROM